ANALISIS KUANTITATIF KESADAHAN TOTAL AIR MINUM ISI ULANG YANG DIJUAL DI WILAYAH KAYU TANGI KOTA BANJARMASIN - Siska Musiam; Siti Darmiani; Aditya Maulana Perdana Putra (jurnal ilmiah manuntung sekolah tinggi ilmu kesehatan samarinda, 2015)
Water is one of the important needs for human body. Therefore, water which consumed should be healthy and have certain quality. One of its quality parameter is total hardness. Total hardness is the hardness which caused by Ca2+ and Mg2+ ions. Hard water, or water with a high level of total hardness, if consumed in long term can lead to hyperparatyroidsm, Nephrolithiasis, and musculusweakness. The aim of this study were to determine total hardness level of refill drinking waterwhich sold in Kayutangi Banjarmasin and to compare it with the standard parameter of total hardness in Permenkes 492/Menkes/IV/2010 which is 500 mg/L in maximum. There were 16 samples in this study that taken from refill drinking water store were found accidentally. The quantitative analysis was done by complexometry titration method with Na2-EDTA as titrant and Eriochrome Black T as indicator. The results showed that the ranges of total hardness level of 16 samples that determined between 35,64 – 99,00 mg/L which is suitable with the standard based on Permenkes 492/Menkes/IV/2010